Antimicrobial Potential of Streptomyces spp. Isolated from the Rift Valley Regions of Ethiopia - Firew Elias; Sudhamani Muddada; Diriba Muleta; Belachew Tefera (Advances in Pharmacological and Pharmaceutical Sciences)
The study was undertaken to isolate, screen, and identify actinomycetes with antimicrobial metabolites. Twenty-one composite soil samples were randomly collected from various unique agroecological niches in the Rift Valley of Ethiopia. The soil samples were serially diluted and spread on starch casein agar medium supplemented with 50 μg/ml cycloheximide and 25 μg/ml nalidixic acid. Two hundred and forty-nine (249) actinomycetes cultures were isolated and screened by cross streaking against various human pathogens. Twenty-four isolates with pronounced antimicrobial activity were selected for identification and further screening. Among the isolates, 172 (69.1%) showed antimicrobial activities against tested pathogens. The inhibition zone of the isolates ranged from 5 ± 0.31 to >40 mm during primary screening. The antimicrobial activity of the crude extracts of promising isolates showed a statistically significant difference P<0.05 between them and the control. The isolates RVE129 and RVE217 showed the maximum zone of inhibition at 27 ± 0.6 mm and 26 ± 0.6 mm, respectively, against S. aureus, and the results were higher than the standard drug streptomycin (25 ± 0.58 mm). The inhibition zone of crude extracts from RVE129 was at the maximum of 22 ± 0.0 mm against P. aeruginosa, almost comparable to the standard drug streptomycin (24 ± 0.58 mm). Crude extract from the isolates RVE129 and RVE187 showed higher inhibition zones of 22 ± 0.6 mm and 16 ± 0.33 mm against A. niger ATCC10535, which, however, were smaller than those obtained with the standard drug amphotericin B (29 ± 0.6 mm). Twenty-four actinomycete strains with remarkable bioactivity were characterized using various cultural, morphological, physiological, and biochemical characteristics and assigned under the genus Streptomycetes. The finding of the current study indicates that Streptomyces sp. isolated from the Rift Valley of Ethiopia was found to possess a broad spectrum of bioactivity against a range of human pathogens.